Göbekli Tepe, Türkei: Die Arbeiten der Jahre 2014 (Herbst) und 2015 - Clare, Lee; Dietrich, Oliver; Notroff, Jens (e-Forschungsberichte des DAI, 2023)
The early Neolithic tell of Göbekli Tepe is situated northeast of the modern town of Şanlıurfa in south-eastern Turkey. Formed by the debris of monumental constructions dating back to the 10th and 9th millennium BC (the Pre-Pottery Neolithic), the mound is excavated systematically since 1995. Recent excavation campaigns focussed on preparative work for the erection of permanent shelter structures to preserve the site.